2019
DOI: 10.1021/acs.macromol.9b01433
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Thermotropic Liquid Crystalline Columnar Mesophases in Stereoregular Polymethylenes with Discotic Triphenylene Side Groups

Abstract: Side-chain discotic liquid crystalline polymers (SDLCPs) with discotic (disclike) mesogens (discogens) attached as side groups through flexible spacers constitute a class of fascinating organic polymer semiconducting materials. While so far almost all reported SDLCPs belong to conventional C2 polymers based on polymerization of vinyl monomers, limiting their structure diversities, substitution density, and efficiency promotion. In this article we present the synthesis of a series of syndiotactic polymethylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
(166 reference statements)
0
10
0
Order By: Relevance
“…For the pre LC-PI I films, an incomplete DSC endothermic peak appears during the heating process, and the peak vertex does not appear before 400 °C. The endothermic peak is due to the gradual transformation of the pre LC-PI I films from amorphous phase to liquid crystal phase . The POM images show that the pre LC-PI I films exhibit no bright spots in the viewshed during the process of heating to 350 °C and the pink color is the background color generated by the crossed polarizer, showing the amorphous state of the samples (Figure a 1 ∼ a 4 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the pre LC-PI I films, an incomplete DSC endothermic peak appears during the heating process, and the peak vertex does not appear before 400 °C. The endothermic peak is due to the gradual transformation of the pre LC-PI I films from amorphous phase to liquid crystal phase . The POM images show that the pre LC-PI I films exhibit no bright spots in the viewshed during the process of heating to 350 °C and the pink color is the background color generated by the crossed polarizer, showing the amorphous state of the samples (Figure a 1 ∼ a 4 ).…”
Section: Resultsmentioning
confidence: 96%
“…The endothermic peak is due to the gradual transformation of the preLC-PI I films from amorphous phase to liquid crystal phase. 53 The POM images show that the preLC-PI I films exhibit no bright spots in the viewshed during the process of heating to 350 °C and the pink color is the background color generated by the crossed polarizer, showing the amorphous state of the samples (Figure 2a 1 ∼a 4 ). When the temperature continues to rise to 400 °C, there are very few scattered bright yellow spots (preLC-PI liquid crystals, Figure 2a 5 ).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The molecular design of 9C n - ester -TCS and 9C n - amide -TCS was inspired by the excellent optical characteristics as well as appealing electrical properties in orderly assembled cyanostilbene derivatives , and was further guided by our experience on discotic columnar LCs. Because the electrical conductivity requires substantial structural rigidity to generate charge transport pathways via intermolecular π–π interactions, while bright luminescence in solid favors distorted molecular conformation to limit nonradiative deactivation, we here designed a quasi-discotic three-arm TCS fluorophore core with specific stereo geometry and moderate π-conjugation effect for the aforementioned issue of synchronous improvement of both conductivity and luminescence performance. X-ray revealed that the star-shaped TCS core exhibits a nonplanar quasi-discotic shape and the phenyl rings adopt a trans conformation relative to one another (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , we herein report a HLCP by employing π-conjugated α-cyanostilbene (CS) as the mesogenic unit, glutamate as the branching point, and decyl chain as the flexible spacer to induce liquid crystallinity. The molecular design was guided by our experience on the hierarchical self-assembly of LC polymers and their fluorescence functionality , and was also benefiting from the two following considerations: (i) Incorporation of noncovalent interactions (such as π–π stacking of the aromatics, , local dipole coupling generated by the lateral polar cyano group, , and hydrogen bond introduced by the glutamate group) in HLCP may promote inter/intramolecular stacking assembly of the CS mesogens and then enable controlled modification of mesomorphic structures by regulation of assembly pathways. (ii) The aggregation-enhanced emission characteristic of the CS mesogen would endow the resulting HLCP with solid-state fluorescence, which is much sensitive to the molecular packing arrangement, thus allowing for an efficient measure in monitoring the mutable assembly structures, and vice versa, providing a way to tune the light emission by structural engineering. , Eventually, the obtained HLCP self-assembled into ordered lamellar smectic phases and exhibited processing-dependent lamellar polymorphism, enabling a control of the molecular packing arrangement in the assembled lamellar arrays and thus a way to tune the multicolored light emission by various processing methods.…”
Section: Introductionmentioning
confidence: 99%